Pelaksanaan Bina Vokalia Di Sanggar Parintang Bukittinggi - Fanny Firgina Aura; Jagar Lumbantoruan (FBS Universitas Negeri Padang, 2020)
This study aims to reveal the phenomena related to vocalia building at Parintang Studio Bukittinggi. These phenomena include sound production techniques, breathing, resonance, intonation, articulation, phrasering, and expression. This study uses a qualitative approach with the object of research was vocalia building at Parintang Studio Bukittinggi. The types of data used were primary and secondary data. The data were collected through literature study, observation, interviews, and documentation. The data analysis was conducted by identifying data, classifying data, clarifying data, analyzing data, describing / explaining data, and concluding. The results of the implementation of vocalia building in Parintang Studio are as follows. The training process at Parintang Studio is doing warming up as basic vocal technique exercise. It includes breathing exercises which are useful for regulating the right breath when singing, resonance exerciseswhich are useful for widening the range of sound, articulation exerciseswhich are useful for clarifying the pronunciation of words, intonation exercises which are useful for improving the ability to read tones, phrasering exerciseswhich are useful for keeping sentences intact, and expression exercises which are useful for expressing the meaning or atmosphere of a song sung. All vocal technique exercises are taught so that students can improve voice processing skills in singing. The obstacle found in the vocational training at Parintang studio is that there are still some student’s voices that are false and not in line with the tempo in singing. The students also do not have confidence. Repeating exercises is the solution made by the instructor to deal with students’ difficulties.